2011
DOI: 10.1186/1472-6963-11-351
|View full text |Cite
|
Sign up to set email alerts
|

Mapping private pharmacies and their characteristics in Ujjain district, Central India

Abstract: BackgroundIn India, private pharmacies are ubiquitous yet critical establishments that facilitate community access to medicines. These are often the first points of treatment seeking in parts of India and other low income settings around the world. The characteristics of these pharmacies including their location, drug availability, human resources and infrastructure have not been studied before. Given the ubiquity and popularity of private pharmacies in India, such information would be useful to harness the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
5
39
0
1
Order By: Relevance
“…GIS is increasingly being used to describe the epidemiology of diseases and to map HCFs for strategic planning of public health measures [4547]. We found that patients living closer to a pharmacy tended to visit facilities more frequently.…”
Section: Discussionmentioning
confidence: 96%
“…GIS is increasingly being used to describe the epidemiology of diseases and to map HCFs for strategic planning of public health measures [4547]. We found that patients living closer to a pharmacy tended to visit facilities more frequently.…”
Section: Discussionmentioning
confidence: 96%
“…However, this proportion is expected to be low; our previous study [17] indicated the rate to be 12%. The studied pharmacies in a single city may have common dispensing patterns.…”
Section: Recommended Approach For the Dispensing Of Antibiotics And Amentioning
confidence: 89%
“…A 2012 census of private pharmacies in the Ujjain district identified 475 pharmacies, of which 387 were urban [17]. The inclusion criteria for this study, urban pharmacies with more than 30 clients per day, were identified from the previous census.…”
Section: Private Pharmaciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in gross violation of the law, most private pharmacies do not have a pharmacist 31. Nearly 50–60% of all clients purchase medicines without a prescription 32 33…”
Section: Global Health Problem Analysismentioning
confidence: 99%